Low-temperature aqueous alteration of chondrites - Lee, M. R.; Alexander, Conel M. O’D.; Bischoff, Addi; Brearley, Adrian J.; Dobrică, Elena; Fujiya, Wataru; Le Guillou, Corentin; King, Ashley J.; van Kooten, Elishevah; Krot, Alexander N.; Leitner, Jan; Marrocchi, Yves; et al. (Space science reviews, 2025)
Chondritic meteorites (chondrites) contain evidence for the interaction of liquid water with the interiors of small bodies early in Solar System history. Here we review the processes, products and timings of the low-temperature aqueous alteration reactions in CR, CM, CI and ungrouped carbonaceous chondrites, the asteroids Ryugu and Bennu, and hydrated dark clasts in different types of meteorites. We first consider the nature of chondritic lithologies and the insights that they provide into alteration conditions, subdivided by the mineralogy and petrology of hydrated chondrites, the mineralogy of hydrated dark clasts, the effects of alteration on presolar grains, and the evolution of organic matter. We then describe the properties of the aqueous fluids and how they reacted with accreted material as revealed by physicochemical modelling and hydrothermal experiments, the analysis of fluid inclusions in aqueously formed minerals, and isotope tracers. Lastly, we outline the chronology of aqueous alteration reactions as determined using the 53Mn-53Cr and 129I-129Xe systems.
Gesehen am 23.10.2025